Knowledge and awareness about oral cancer among dental patients in Southeastern Anatolia (Annals of Medical Research, 2021)
Aim: The aim of this study is to assess the levels of knowledge and awareness of dental patients in South-Eastern Anatolian on oral cancer.Material and Methods: This study conducted with 389 (209 females and 180 males) participants. Sociodemographic information such as age, gender, education level, living place, smoking and alcohol use were obtained from dental patients. A questionnaire including early signs and risk factors related to the disease to assess the knowledge and awareness about oral cancer was performed. Obtained data were statistically analyzed with descriptive analyses, independent t sample test and ANOVA.Results: Only 23.1% of participants had heard of oral cancer. Smoking (95.5%), alcohol (68.7%) and tobacco use (67.9%) were the most often identified risk factors of oral cancer, whereas heavy sun exposure (12.1%) was the least defined factor. There was a statistically significant difference between education level and living place for awareness of oral cancer (p 0.05). As the source of the information for oral cancer, the television and internet were the first while the medical doctors were the last.Conclusion: This study demonstrated that knowledge and awareness about the oral cancer were insufficient in South-Eastern Anatolian. There is a substantial need to raise awareness of oral cancer, its risk factors, and early signs of the disease. Visual media, billboards and information leaflets may be useful for this issue.
Keywords: Oral cancer; knowledge; awareness; risk factors; dentistry; patients